A Novel Osteoclast Precursor Cell Line, 4B12, Recapitulates the Features of Primary Osteoclast Differentiation and Function: Enhanced Transfection Efficiency Before and After Differentiation - Amano, Shigeru (2009)
Osteoclasts are bone-resorbing multinucleated cells differentiated from monocyte/macrophage lineage precursors. A novel osteoclast precursor cell line, 4B12 was established from Mac-1(+)c-Fms(+)RANK(+) cells from calvaria of 14-day-old mouse embryos using immunofluorescence and cell-sorting methods. Like M-CSF-dependent bone marrow macrophages (M-BMMs), M-CSF is required for 4B12 cells to differentiate into TRAP-positive multinucleated cells [TRAP(+) MNCs] in the presence of RANKL. Bone-resorbing osteoclasts differentiated from 4B12 cells on dentine slices possess both a clear zone and ruffled borders and express osteoclast-specific genes. Bone-resorbing activity, but not TRAP, was enhanced in the presence of IL-1α. The number of TRAP(+) MNCs and the number of pits formed from 4B12 cells on dentine slices was four-fold higher than that from M-BMMs. 4B12 cells were identified as macrophages with Mac-1 and F4/80, yet lost these markers upon differentiation into osteoclasts as determined by confocal laser scanning microscopy. The 4B12 cells do not have the potential to differentiate into dendritic cells indicating commitment to the osteoclast lineage. 4B12 cells are readily transfectable with siRNA transfection before and after differentiation. These data show that 4B12 cells faithfully replicate the properties of primary cells and are a useful and powerful model for analyzing the molecular and cellular regulatory mechanisms of osteoclastogenesis and osteoclast function.